STILISTIKA DIALOG QUR’ANI DALAM KISAH NABI NUH AS. - Asep Sopian (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
Abstract: This research confirms that the language style used in the narratives of Alquran is theistic style, which varies depending on the context and the theme as well as the contemporary relevance. This research aims to (a) describe the style of Noah’s narrative in Alquran; (b) describe the stylistics of the elements forming the dialogues of Prophet Noah’s narrative; and (c) uncover as well as describe the meaning and the impression of Quranic dialgues in the narrative of Prophet Noah.This study is qualitative research. Meanwhile, based on the object of the study and thegoal to obtain, this study belongs to library research assessed with content analysis. Thus, this study focuses on literary data sources, namely all kinds of documents or other written sources, such as scientific books, journals, acrhives, private documents, and other written articles.Based on the findings and the analysis, it is concluded that (1) Noah’s narrative is presented in various surahs to show the authenticity and peculiarity of Quranic uslub; (2) the diction and the coresponding placement of the words are appropriate and varied, and the uslub described are also varied; and (3) the narrative described offers great significance and deep impression to strengthen the tauhid, patience, the fight between right and wrong, and severe punishments subjected to unbelievers.Permalink/DOI: dx.doi.org/10.17977/um015v45i22017p181